Comparative Activity of Carbapenem Antibiotics Against Gram-Negative Carbapenemase Producers of Diﬀerent Groups - V. A. Ageevets; O. S. Sulian; A. A. Avdeeva; P. S. Chulkova; V. V. Gostev; I. V. Ageevets; M. V. Golikova; K. N. Alieva; D. P. Gladin; S. V. Sidorenko (Антибиотики и Химиотерапия, 2022)
The rapid spread of gram-negative bacteria resistance to carbapenems due to the production of carbapenemases requires new treatment options. The activity of carbapenem antibiotic biapenem, recently registered in Russia, against producers of various carbapenemases was studied in comparison with other antibiotics of this group. Among NDM-type carbapenemase producers, 77.8% demonstrated clinical susceptibility to biapenem; 50.3% and 21.1% of isolates were susceptible to meropenem and imipenem, respectively. Among the producers of OXA-48-type carbapenemases, 82,6%, 60,9%, and 65,2% of isolates demonstrated susceptibility to biapenem, imipenem, and meropenem, respectively.Producers of KPC-type carbapenemases were 100% resistant to all carbapenems. The introduction of biapenem will signiﬁcantly expand the possibilities of treating severe infections caused by carbapenemase producers.